Is psychological treatment equally effective for intimate partner violence perpetrators with and without childhood family violence? - Fernández-Montalvo, Javier (Legal and criminological psychology, 2021)
Purpose This study assessed the differential long-term effectiveness of a standard treatment programme for intimate partner violence male perpetrators (IPV-P), depending on the presence of childhood family violence (CFV). Methods A sample of 1,008 male IPV-P were included in the study. Comparisons between men with CFV (n = 339) and without CFV (n = 669) on sociodemographic characteristics and psychopathological variables were carried out at pre-treatment. The differential effectiveness of the treatment was assessed at post-treatment and at 1-year follow-up. Results The pre-treatment assessment showed that IPV-P with CFV had a lower level of education, higher rates of previous psychiatric history, and more voluntary access to the treatment. Moreover, they began the treatment programme with more psychopathological symptoms, assessed by the SCL-90-R and STAXI-2. Regarding treatment results, the attrition rates did not reach significant differences between groups. The repeated-measures ANOVA evidenced statistically significant improvement in psychopathological symptoms on most of the variables for both groups. However, comparisons between groups on psychopathological symptoms showed that IPV-P with CFV were affected to a significantly higher degree on many variables at post-treatment and follow-up, although no differences were found in the global rates of treatment outcomes. Conclusions This investigation highlights the heterogeneity of IPV-P and the differential progression along the treatment programmes according to the presence of CFV.